ASSESSMENT OF THE PRODUCTIVITY OF FISHERY IN LENTIC AQUASYSTEM FROM A SCORE OF BIO-SOCIAL AND TECHNO MANAGERIAL FACTORS - PAIK, T. K.; ACHARYA, S. K.; CHAKRABORTY, S. K.; BISWAS, S.; HAQUE, A. (Journal of the Inland Fisheries Society of India, 2022)
Lentic aqua-system is the largest ecosystem for managing inland fishery. The productivity at fishery in such aqua-system presupposes the befitting performance from the social, economics and management subsystem.Alongside the technological dimension, the issues of livelihood and income generation are equally important. The present study envisages fish productivity as a collateral contribution made by a score of causal factors. The study carried out in some blocks of North 24 Pgs in W.B. depicted that the technomanagerial factors like water area (X7)pH of pond area (X12), plankton quantity (X13), dissolved O2 (X15), stocking density (X17), cost of input (X18), size of the fry (X19) had recorded significant association in fish productivity. Multiple regression analysis evince that plankton quality (X13), stocking density (X17), cost of input (X18), size of fry (X19) and gross investment also exerted predominant causal impacts on the fish productivity.